Modelling the final cost of construction projects in Kingdom of Bahrain - MOHAMMED, BADER NASSER (2017)
The report aimed at providing the insight towards the various factors in the construction industry which add up to the cost of the project. The report identifies the relation of the project cost with several factors which are considered to be dependable or independent. The research work recognizes the importance of every single dependent, and independent factor and the analysis based on data interpretation helped to locate the various areas which influence the overall project cost in the construction industry. For better vision to the effect on cost, the report submits the analytical data such as graphs and tables which were determined on researching over the base of previous research work.